Strongest drivers of trust in automotive supply chains - Tolmay, Aletta S. (Logistics, supply chain, sustainability and global challenges, 2025)
The issue addressed in this paper concerns the erosion of trust within supply chains, as reported by key industry stakeholders. In this context, automotive component buyers frequently rely on single-source suppliers, thereby intensifying competitive pressures on component manufacturers. Consequently, automotive component suppliers must seek to strengthen supplier relationships to enhance trust. Given the limited opportunities for differentiation, automotive component suppliers increasingly pursue alternative strategies to ensure their long-term sustainability, with a particular emphasis on value-driven supplier relationships founded on trust. Existing literature suggests that optimised supplier relationships contribute to trust-building. This study employs a quantitative approach, utilising path analysis to identify the relationship value construct exhibiting the strongest correlation with trust. The findings indicate a significant correlation between product quality and delivery, suggesting that the timely and accurate delivery of products is the most critical factor in fostering trust between buyers and suppliers. Additionally, the analysis reveals that the most statistically significant aspect of relationship value is product quality and delivery. The paper concludes with theoretical and managerial recommendations, including the implementation of a relational governance strategy within automotive supply chains to strengthen trust and enhance long-term sustainability.
Keywords: buyer-seller relationships; južnoafriška avtomobilska industrija; odnosi med kupci in prodajalci; odnosi v oskrbovalni verigi; relationship governance; South African automotive industry; supply chain relationships; upravljanje odnosov; zaupanje